Gastrointestinal symptoms in pregnancy among antenatal clinic attendees in Abubakar Tafawa Balewa University Teaching Hospital Bauchi, Northeast Nigeria - Aminu, Muhammad Baffah; Alkali, Mohammed; Audu, Bala M.; Abdulrazak, Toyin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pregnant women are at increasing risk of GI symptoms such as nausea, vomiting and heartburns, most of these symptoms are as a result of the hormonal and physical changes associated with pregnancy. This study aimed to determine prevalence of gastrointestinal symptoms (GI) among pregnant women attending booking clinic at a Northeastern Nigerian Teaching Hospital. Methods: The study was a cross-sectional, questionnaire-based survey of four hundred and fifty-two pregnant women booking for antenatal care. Their sociodemographic variables as well as the presence or absence of gastrointestinal symptoms in index pregnancy were obtained at by the use of researcher-administered questionnaire. Data were analyzed and presented as frequencies and percentages. A 5% significance level (p <0.05) to test associations. Results: Two fifty-five women had heart burns (56.4%) while 235 (52.0%) had nausea in pregnancy, these were observed to be the most prevalent GI symptoms among the women. Diarrhea and hemorrhoids were the uncommon GI symptoms in the study population constituting 406 (89.5%), and 360 (79.6%) respectively. Easy fullness was noted in 39.8% of the women while vomiting was in 41.8% and constipation in 29% of the respondents. A significant association was observed (p value <0.05) between parity and development of anorexia and hemorrhoids in pregnancy (p values of 0.049 and 0.051 respectively) but not for the other symptoms. Conclusions: GI symptoms are common in pregnancy, the most prevalent symptoms are that of heart burns and nausea, while diarrhea is relatively uncommon.